TP5.2.6 Use of objective assessment criteria to assess symptom severity and clinical effectiveness following deep venous stenting. (28th October 2021) - Ghulam, Mustafa; Lodhia, Krishan; Carter, Jemima; Saratzis, Athanasios; Saha, Prakash
Abstract: Aims: This review aimed to identify measures that assess symptom severity in patients prior to deep venous intervention, and outcomes used to evaluate its clinical effectiveness. Methods: MEDLINE was searched for studies of stent placement for treatment of iliofemoral venous disease using relevant key words (April 2019). Data were extracted and validated by three authors. Results: 6, 356 patients with venous stents were identified from 93 studies. 1, 300 patients (20%) were treated for acute thrombosis and 5, 056 patients for chronic venous insufficiency (CVI), due to non-thrombotic lesions (2, 200 patients, 35%) or post-thrombotic disease (2, 856 patients, 45%). The Clinical-Etiological-Anatomical-Physiological classification (CEAP) was reported in 3, 233/5, 056 CVI patients (64%) pre-intervention (C0:2%; C1:2%; C2:7%; C3:46%; C4:21%; C5:6%; C6:16%). Stent patency was reported in all studies, with variable follow-up (six months – five years). Primary patency was 81% in 3, 365 patients and secondary patency 95% in 4, 700 patients at one year. 655 patients had active ulceration, of which 397 (61%) healed post-intervention. Venous Clinical Severity Score (VCSS) or revised VCSS was reported in 849 patients (13%). Average VCSS/rVCSS was eight pre-intervention and three post-intervention. Villalta scores were reported in 768 patients (12%) pre-intervention vs. 1, 111 patients (17%) post-intervention. Average Villalta scores were 20 pre-intervention vs. five post-intervention. Conclusions: Few studies use objective measures to quantify the clinical effectiveness of deep venous stenting; consensus is lacking on which is the most appropriate tool to use. More research is needed on ideal assessment measures to identify suitable patients for these interventions and to quantify clinical effectiveness.